IMPLEMENTATION OF FAN-N-PICK COOPERATIVE LEARNING STRATEGY ON STUDENTS’ INTEREST IN READING COMPREHENSION - Muhammad Isgaf; Fathurrahman Imran; K. Dedy Sandiarsa S. (Sinar Lima, 2024)
This inquiries about pointed to discover out whether or not the execution of the Fan-N-Pick agreeable learning technique encompasses a positive impact on students intrigued in perusing comprehension in eleventh review at SMKN 1 Mataram. This inquiries about utilized pre- experimental with post-test-only plan or inactive gather plan. The populace in this think about was 60 understudies, comprising of lesson XITB1 with 30 understudies and class XITB2 with 30 understudies, the analyst took the complete populace as a test utilizing add up to inspecting strategies. The instrument utilized in this considers was a survey that was utilized to get information approximately the usage of the Fan-N-Pick agreeable learning technique toward the eleventh-grade students' interest in perusing comprehension. In this investigate, the analyst collected the information by employing a survey, and the sort of survey strategy utilized a closed survey. Based on information examination by utilizing SPSS computer program it was found that the esteem of Sig. (2-tailed) was 0.001< 0>0.05). It can be concluded that the Fan-N-Pick procedure is fitting for moving forward students' perusing comprehension capacities. The Fan-N- Pick methodology makes a difference understudies know specifically the meaning of outside words, it is more dynamic in lesson and makes a difference understudies alter their considering efficiently from common to particular, and the Fan-N-Pick procedure features a positive impact on students' interest in Reading Comprehension.